Home page for accesible maths 9 Workshop Solutions

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

9.2 Workshop Solutions 2

True or False? (i) False. For example, let f(x)=1xf(x)=\frac{1}{x}, then 1Rdxx=[logx]1R=logR\int_{1}^{R}\frac{dx}{x}=\left[\log x\right]_{1}^{R}=\log R\rightarrow\infty as RR\rightarrow\infty.

(ii) False, e.g. f(x)=1xf(x)=\frac{1}{x}. (See 1.54 in the notes.)

(iii) True, by the comparison test, since |e-xx2|1x2\left|\frac{e^{-x}}{x^{2}}\right|\leq\frac{1}{x^{2}} for x1x\geq 1, so by the comparison test (1.57) 1e-xx2dx\int_{1}^{\infty}\frac{e^{-x}}{x^{2}}\,dx converges and has absolute value less than or equal to 1dxx2=1\int_{1}^{\infty}\frac{dx}{x^{2}}=1.

(iv) False. All we can say is that ff is a function of yy only. For example, we could have f(x,y)=yf(x,y)=y.

W2.1. i) We combine the logs to get

12log(R2+2)-log(3R+1)=12logR2+2(3R+1)2=12logR2+29R2+6R+112log19{{1}\over{2}}\log(R^{2}+2)-\log(3R+1)={{1}\over{2}}\log{{R^{2}+2}\over{(3R+1)^% {2}}}={{1}\over{2}}\log{{R^{2}+2}\over{9R^{2}+6R+1}}\rightarrow{{1}\over{2}}% \log{{1}\over{9}}

as RR\rightarrow\infty. Thus the limit of the expression as RR\rightarrow\infty is -log3-\log 3.

ii) In this case, if we combine logs then we obtain log(R3-3)-2log(R-1)=logR3-3(R-1)2=logR3-3R2-2R+1\log(R^{3}-3)-2\log(R-1)=\log\frac{R^{3}-3}{(R-1)^{2}}=\log{R^{3}-3}{R^{2}-2R+1}. We have to cancel the same power on top and bottom, so this is equal to logR-3/R21-2/R+1/R2\log\frac{R-3/R^{2}}{1-2/R+1/R^{2}}. The expression inside the log\log tends to \infty as RR\rightarrow\infty, and therefore this expression diverges.

iii) In this case we combine everything into a single logarithm to obtain log(4R3-1)2(7R5-2)(3R-2)\log\frac{(4R^{3}-1)^{2}}{(7R^{5}-2)(3R-2)}. The highest degree term in RR on both top and bottom is R6R^{6}, hence this logarithm equals

log(4-1/R3)2(7-2/R5)(3-2/R)=log4221=log1621.\log\frac{(4-1/R^{3})^{2}}{(7-2/R^{5})(3-2/R)}=\log\frac{4^{2}}{21}=\log\frac{% 16}{21}.

iv) We have R+1R2-1=1R-1\frac{R+1}{R^{2}-1}=\frac{1}{R-1} and hence the expression simplifies to 1R-1log(R-1)\frac{1}{R-1}\log(R-1). Now we can replace RR by R+1R+1 without affecting convergence or divergence of this expression, so the question simplifies further to finding the limit of 1RlogR=-1Rlog1R\frac{1}{R}\log R=-\frac{1}{R}\log\frac{1}{R} as RR\rightarrow\infty. By 4.23.1 in MATH101, xlogx0x\log x\rightarrow 0 as x0+x\rightarrow 0+, so substituting x=1Rx=\frac{1}{R} we obtain that the limit of the function is 00.

The technically correct way to do these is to simplify,

then take limits at the last step.

W2.2. (i) We use partial fractions, and find that

1(x+3)(5x+1)=Ax+3+B5x+1{{1}\over{(x+3)(5x+1)}}={{A}\over{x+3}}+{{B}\over{5x+1}}

when

1=A(5x+1)+B(x+3),1=A(5x+1)+B(x+3),

which gives the simultaneous equations for the coefficients

x:0=5A+B1=-14AA=-1/141:1=A+3B0=5A+BB=5/14.\begin{matrix}x:0=5A+B&&1=-14A&&A=-1/14\cr 1:1=A+3B&&0=5A+B&&B=5/14.\cr\end{matrix}

The integral to consider is

0Rdx(x+3)(5x+1)=0R(-1/14x+3+5/145x+1)dx=[-114log(x+3)+114log(5x+1)]0R\int_{0}^{R}{{dx}\over{(x+3)(5x+1)}}=\int_{0}^{R}\Bigl({{-1/14}\over{x+3}}+{{5% /14}\over{5x+1}}\Bigr)dx=\Bigl[-{{1}\over{14}}\log(x+3)+{{1}\over{14}}\log(5x+% 1)\Bigr]_{0}^{R}
=114(-log(R+3)+log(5R+1))-114(-log3+log1)={{1}\over{14}}\Bigl(-\log(R+3)+\log(5R+1)\Bigr)-{{1}\over{14}}\Bigl(-\log 3+% \log 1\Bigr)
=114log5R+1R+3+114log3114log5+114log3asR={{1}\over{14}}\log{{5R+1}\over{R+3}}+{{1}\over{14}}\log 3\rightarrow{{1}\over% {14}}\log 5+{{1}\over{14}}\log 3\;\;\mbox{as}\;\;R\rightarrow\infty

since (5R+1)/(R+3)5(5R+1)/(R+3)\rightarrow 5.

Hence the integral converges and

0dx(x+3)(5x+1)=114log15.\int_{0}^{\infty}{{dx}\over{(x+3)(5x+1)}}={{1}\over{14}}\log 15.

(ii) In this case there are factors involving 11 and x2x^{2}, but not xx itself, so the relevant partial fraction decomposition is simply

1x2(4+x2)=Ax2+B4+x2,{{1}\over{x^{2}(4+x^{2})}}={{A}\over{x^{2}}}+{{B}\over{4+x^{2}}},

which reduces to

1=A(4+x2)+Bx21=A(4+x^{2})+Bx^{2}

and hence the simultaneous equations for the coefficients

x2:0=A+BA=1/41:1=4AB=-1/4.\begin{matrix}x^{2}:0=A+B&&A=1/4\cr 1:1=4A&&B=-1/4.\cr\end{matrix}

Hence we consider the integral

2Rdxx2(4+x2)=2R(1/4x2-1/44+x2)dx=[-14x-18tan-1x2]2R\int_{2}^{R}{{dx}\over{x^{2}(4+x^{2})}}=\int_{2}^{R}\Bigl({{1/4}\over{x^{2}}}-% {{1/4}\over{4+x^{2}}}\Bigr)dx=\Bigl[-{{1}\over{4x}}-{{1}\over{8}}\tan^{-1}{{x}% \over{2}}\Bigr]_{2}^{R}
=-14R-18tan-1R/2-(-18-18tan-11)=-14R-18tan-1R/2+18+π32-π16+18+π32=-{{1}\over{4R}}-{{1}\over{8}}\tan^{-1}R/2-\Bigl({{-1}\over{8}}-{{1}\over{8}}% \tan^{-1}1\Bigr)=-{{1}\over{4R}}-{{1}\over{8}}\tan^{-1}R/2+{{1}\over{8}}+{{\pi% }\over{32}}\rightarrow-{{\pi}\over{16}}+{{1}\over{8}}+{{\pi}\over{32}}

as RR\rightarrow\infty. Hence the integral converges to

2dxx2(4+x2)=18-π32.\int_{2}^{\infty}{{dx}\over{x^{2}(4+x^{2})}}={{1}\over{8}}-{{\pi}\over{32}}.

W2.3. By the answer to W1.5(iv), we have

2R26f(x)dx=[12log(x2-2x+10x2-4x+8)-23tan-1(x-13)+32tan-1(x-22)]2R\int_{2}^{R}\frac{26}{f(x)}dx=\left[\frac{1}{2}\log\left(\frac{x^{2}-2x+10}{x^% {2}-4x+8}\right)-\frac{2}{3}\tan^{-1}\left(\frac{x-1}{3}\right)+\frac{3}{2}% \tan^{-1}\left(\frac{x-2}{2}\right)\right]_{2}^{R}
=12log(R2-2R+10R2-4R+8)-23tan-1(R-13)+32tan-1(R-22)-12log104+23tan-113-32tan-10.=\frac{1}{2}\log\left(\frac{R^{2}-2R+10}{R^{2}-4R+8}\right)-\frac{2}{3}\tan^{-% 1}\left(\frac{R-1}{3}\right)+\frac{3}{2}\tan^{-1}\left(\frac{R-2}{2}\right)-% \frac{1}{2}\log\frac{10}{4}+\frac{2}{3}\tan^{-1}\frac{1}{3}-\frac{3}{2}\tan^{-% 1}0.

Since R2-2R+10R2-4R+8=1-2/R+10/R21-4/R+8/R211=1\frac{R^{2}-2R+10}{R^{2}-4R+8}=\frac{1-2/R+10/R^{2}}{1-4/R+8/R^{2}}\rightarrow% \frac{1}{1}=1 as RR\rightarrow\infty, the first term tends to zero. Further, tan-1(R-13)\tan^{-1}\left(\frac{R-1}{3}\right) and tan-1(R-22)\tan^{-1}\left(\frac{R-2}{2}\right) both tend to π2\frac{\pi}{2} as RR\rightarrow\infty, so the integral converges to

(32-23)π2-12log104+23tan-113=5π12+log210+23tan-113.(\frac{3}{2}-\frac{2}{3})\frac{\pi}{2}-\frac{1}{2}\log\frac{10}{4}+\frac{2}{3}% \tan^{-1}\frac{1}{3}=\frac{5\pi}{12}+\log\frac{2}{\sqrt{10}}+\frac{2}{3}\tan^{% -1}\frac{1}{3}.

W2.4. i) This is an improper integral since 1x\frac{1}{\sqrt{x}}\rightarrow\infty as x0+x\rightarrow 0+. Thus we consider δ1dxx=[2x]δ1=2(1-δ)2\int_{\delta}^{1}\frac{dx}{\sqrt{x}}=\left[2\sqrt{x}\right]_{\delta}^{1}=2(1-% \sqrt{\delta})\rightarrow 2 as δ0+\delta\rightarrow 0+. Therefore the integral converges to 22. (This is just a special case of Example 1.54 in the notes.)

ii) This is an improper integral as 4-x20\sqrt{4-x^{2}}\rightarrow 0 as x2-x\rightarrow 2-. To evaluate this integral we make the substitution x=2sintx=2\sin t. Then the limits of integration change as: t=0t=0 when x=0x=0, t=sin-1(1-δ2)t=\sin^{-1}(1-\frac{\delta}{2}) when x=2-δx=2-\delta. Further, dxdt=2cost\frac{dx}{dt}=2\cos t and cost\cos t is positive for this range of values of tt, so 4-x2=4-4sin2t=2cost\sqrt{4-x^{2}}=\sqrt{4-4\sin^{2}t}=2\cos t. Thus

02-δdx4-x2=0sin-1(1-δ2)2costdt2cost=sin-1(1-δ2)sin-11=π2\int_{0}^{2-\delta}\frac{dx}{\sqrt{4-x^{2}}}=\int_{0}^{\sin^{-1}(1-\frac{% \delta}{2})}\frac{2\cos t\,dt}{2\cos t}=\sin^{-1}(1-\frac{\delta}{2})% \rightarrow\sin^{-1}1=\frac{\pi}{2}

as δ0+\delta\rightarrow 0+.

Taking the bounds 0x2-δ0\leq x\leq 2-\delta rather than 0x20\leq x\leq 2 is the formally correct way to check this integral.

iii) This is an improper integral as x2-40\sqrt{x^{2}-4}\rightarrow 0 as x2+x\rightarrow 2+. To evaluate the integral we make the substitution x=2coshtx=2\cosh t. Then the bounds of integration change as: t=cosh-1(1+δ2)t=\cosh^{-1}(1+\frac{\delta}{2}) when x=2+δx=2+\delta; t=cosh-12t=\cosh^{-1}2 when x=4x=4. Also, dxdt=2sinht\frac{dx}{dt}=2\sinh t and sinht\sinh t is positive for this range of values of tt, so that x2-4=4sinh2t=2sinht\sqrt{x^{2}-4}=\sqrt{4\sinh^{2}t}=2\sinh t. Therefore

2+δ4dxx2-4=cosh-1(1+δ2)cosh-122sinhtdt2sinht=(cosh-12-cosh-1(1+δ2))cosh-12\int_{2+\delta}^{4}\frac{dx}{\sqrt{x^{2}-4}}=\int_{\cosh^{-1}(1+\frac{\delta}{% 2})}^{\cosh^{-1}2}\frac{2\sinh t\,dt}{2\sinh t}=(\cosh^{-1}2-\cosh^{-1}(1+% \frac{\delta}{2}))\rightarrow\cosh^{-1}2

as δ0+\delta\rightarrow 0+.

iv) This is an improper integral as 1+cosx=01+\cos x=0 when x=πx=\pi. Thus 11+cosx\frac{1}{1+\cos x}\rightarrow\infty as xπx\rightarrow\pi.

This is a rational function of cosx\cos x so the standard way to evaluate the integral is via the substitution t=tanx2t=\tan\frac{x}{2}. However, a quicker way to determine this integral is by the observation: 1+cosx=1+(2cos2x2-1)=2cos2x21+\cos x=1+(2\cos^{2}\frac{x}{2}-1)=2\cos^{2}\frac{x}{2}. Therefore

0π-δdx1+cosx=0π-δ12sec2x2dx=[tanx2]0π-δ=tanπ-δ2\int_{0}^{\pi-\delta}\frac{dx}{1+\cos x}=\int_{0}^{\pi-\delta}\frac{1}{2}\sec^% {2}\frac{x}{2}\,dx=\left[\tan\frac{x}{2}\right]_{0}^{\pi-\delta}=\tan\frac{\pi% -\delta}{2}\rightarrow\infty

as δ0+\delta\rightarrow 0+. Thus the integral diverges.

v) This is an improper integral for the same reason as in (iv). Furthermore, in order for the integral 02πdx1+cosx\int_{0}^{2\pi}\frac{dx}{1+\cos x} to converge, we need both 0πdx1+cosx\int_{0}^{\pi}\frac{dx}{1+\cos x} and π2πdx1+cosx\int_{\pi}^{2\pi}\frac{dx}{1+\cos x} to converge. Therefore the integral diverges.

This example shows that one should be careful about points of discontinuity inside the range of integration. A naive approach to this question would produce the answer 02πdx1+cosx=[tanx2]02π=0\int_{0}^{2\pi}\frac{dx}{1+\cos x}=\left[\tan\frac{x}{2}\right]_{0}^{2\pi}=0, which is certainly not right!

W2.5. The Laplace transform is

F(s)=0e-sxf(x)dx.F(s)=\int_{0}^{\infty}e^{-sx}f(x)dx.

When f(x)=coshaxf(x)=\cosh ax and s>a>0s>a>0, we can calculate

0Re-sxcoshaxdx=0Re-sx12(eax+e-ax)dx=120R(e-(s-a)x+e-(s+a)x)dx\int_{0}^{R}e^{-sx}\cosh ax\,dx=\int_{0}^{R}e^{-sx}{{1}\over{2}}\bigl(e^{ax}+e% ^{-ax}\bigr)dx={{1}\over{2}}\int_{0}^{R}\bigl(e^{-(s-a)x}+e^{-(s+a)x}\bigr)dx
=12[-e-(s-a)xs-a-e-(s+a)xs+a]0R=12[1s-a+1s+a-e-(s-a)Rs-a-e-(s+a)Rs+a]12[1s-a+1s+a]={{1}\over{2}}\Bigl[-{{e^{-(s-a)x}}\over{s-a}}-{{e^{-(s+a)x}}\over{s+a}}\Bigr]% _{0}^{R}={{1}\over{2}}\Bigl[{{1}\over{s-a}}+{{1}\over{s+a}}-{{e^{-(s-a)R}}% \over{s-a}}-{{e^{-(s+a)R}}\over{s+a}}\Bigr]\rightarrow{{1}\over{2}}\Bigl[{{1}% \over{s-a}}+{{1}\over{s+a}}\Bigr]

as RR\rightarrow\infty. Hence

F(s)=ss2-a2  (s>a).F(s)={{s}\over{s^{2}-a^{2}}}\qquad(s>a).

Whereas the calculation by integration by parts as in the trigonometric integrals is possible, it is much more painful. It is also possible to use the fact that the Laplace transform of sinhax\sinh ax is as2-a2\frac{a}{s^{2}-a^{2}} and Prop. 6.42 in the notes.

W2.6. We have ax=exlogaa^{x}=e^{x\log a}. Thus

0Raxdx=0Rexlogadx=[1logaexloga]0R=1loga(aR-a0).\int_{0}^{R}a^{x}\,dx=\int_{0}^{R}e^{x\log a}\,dx=\left[\frac{1}{\log a}e^{x% \log a}\right]_{0}^{R}=\frac{1}{\log a}\left(a^{R}-a^{0}\right).

Now aR0a^{R}\rightarrow 0 as RR\rightarrow\infty and a0=1a^{0}=1, so 0axdx=-1loga\int_{0}^{\infty}a^{x}\,dx=-\frac{1}{\log a}.

W2.7. (i) Let u=x2/2u=x^{2}/2, so that dudx=x{{du}\over{dx}}=x, and

x|aRu|a2/2R2/2\begin{matrix}x&|&a&R\cr u&|&a^{2}/2&R^{2}/2\cr\end{matrix}

and substitute this into the integral to obtain

0Rxe-x2/2dx=a2/2R2/2e-udu=[-e-u]a2/2R2/2=e-a2/2-e-R2/2e-a2/2\int_{0}^{R}xe^{-x^{2}/2}dx=\int_{a^{2}/2}^{R^{2}/2}e^{-u}du=\Bigl[-e^{-u}% \Bigr]_{a^{2}/2}^{R^{2}/2}=e^{-a^{2}/2}-e^{-R^{2}/2}\rightarrow e^{-a^{2}/2}

as RR\rightarrow\infty; hence

axe-x2/2dx=e-a2/2.\int_{a}^{\infty}xe^{-x^{2}/2}dx=e^{-a^{2}/2}.

(ii) We write e-x2/2=x-1(xe-x2/2)e^{-x^{2}/2}=x^{-1}\bigl(xe^{-x^{2}/2}\bigr) and integrate by parts to obtain

aRe-x2/2dx=aRx-1(xe-x2/2)dx=[-x-1e-x2/2]aR-aRx-2e-x2/2dx.\int_{a}^{R}e^{-x^{2}/2}dx=\int_{a}^{R}x^{-1}\bigl(xe^{-x^{2}/2}\bigr)dx=\bigl% [-x^{-1}e^{-x^{2}/2}\bigr]_{a}^{R}-\int_{a}^{R}x^{-2}e^{-x^{2}/2}dx.

We have R-1e-R2/20R^{-1}e^{-R^{2}/2}\rightarrow 0 as RR\rightarrow\infty, and the integral ax-2e-x2/2dx\int_{a}^{\infty}x^{-2}e^{-x^{2}/2}dx converges since ax-2dx\int_{a}^{\infty}x^{-2}dx converges; hence we can let RR\rightarrow\infty in the preceding identity and obtain

ae-x2/2dx=1ae-a2/2-a1x2e-x2/2dx.\int_{a}^{\infty}e^{-x^{2}/2}dx={{1}\over{a}}e^{-a^{2}/2}-\int_{a}^{\infty}{{1% }\over{x^{2}}}e^{-x^{2}/2}dx.

Hermite showed that the integral ae-x2/2dx\int_{a}^{\infty}e^{-x^{2}/2}dx cannot be expressed in closed form in terms of elementary functions, where by ‘closed form’ we mean that no limits or other integrals are involved. As this integral arises in many applications, such as to the normal random variable in statistics, it is important to have techniques for estimating the numerical value of the integral.

W2.8. (i) If f(x,y)=sinxcoshyf(x,y)=\sin x\cosh y then fx=cosxcoshy\frac{\partial f}{\partial x}=\cos x\cosh y and fy=sinxsinhy\frac{\partial f}{\partial y}=\sin x\sinh y.

(ii) If g(x,y)=cosxsinhyg(x,y)=\cos x\sinh y then gx=-sinxsinhy{{\partial g}\over{\partial x}}=-\sin x\sinh y and gy=cosxcoshy{{\partial g}\over{\partial y}}=\cos x\cosh y.

W2.9. (i) The various first-order partial derivative of f=zsinh(yz3+x2)f=z\sinh(yz^{3}+x^{2}) are

fx=2xzcosh(yz3+x2), fy=z4cosh(yz3+x2), fz=sinh(yz3+x2)+3yz3cosh(yz3+x2).{{\partial f}\over{\partial x}}=2xz\cosh(yz^{3}+x^{2}),\;{{\partial f}\over{% \partial y}}=z^{4}\cosh(yz^{3}+x^{2}),\;{{\partial f}\over{\partial z}}=\sinh(% yz^{3}+x^{2})+3yz^{3}\cosh(yz^{3}+x^{2}).

(ii) If

g(x,y,z)=ex+2y+3zg(x,y,z)=e^{x+2y+3z}

then

gx=ex+2y+3z, gy=2ex+2y+3z,gz=3ex+2y+3z.{{\partial g}\over{\partial x}}=e^{x+2y+3z},\;{{\partial g}\over{\partial y}}=% 2e^{x+2y+3z},{{\partial g}\over{\partial z}}=3e^{x+2y+3z}.

W2.10. The function u(x,t)=sin(x2-t)u(x,t)=\sin(x^{2}-t) has

ux=2xcos(x2-t)andut=-cos(x2-t),{{\partial u}\over{\partial x}}=2x\cos(x^{2}-t)\quad{\hbox{and}}\quad{{% \partial u}\over{\partial t}}=-\cos(x^{2}-t),

hence

ux+2xut=0.{{\partial u}\over{\partial x}}+2x{{\partial u}\over{\partial t}}=0.

W2.11. Set f=x+y5+z7f=x+y^{5}+z^{7}, so that w=f6w=f^{6}. Note that fx=1\frac{\partial f}{\partial x}=1, fy=5y4\frac{\partial f}{\partial y}=5y^{4} and fz=7z6\frac{\partial f}{\partial z}=7z^{6}. By the product rule,

x(f6)=6f5fx=6f5\frac{\partial}{\partial x}\left(f^{6}\right)=6f^{5}\frac{\partial f}{\partial x% }=6f^{5}

Now wxy=(wx)y=y(wx)=6y(f5)w_{xy}=(w_{x})_{y}=\frac{\partial}{\partial y}\left(w_{x}\right)=6\frac{% \partial}{\partial y}\left(f^{5}\right). Using the product rule again, y(f5)=5f4fy=25y4f4\frac{\partial}{\partial y}\left(f^{5}\right)=5f^{4}\frac{\partial f}{\partial y% }=25y^{4}f^{4}. Hence wxy=150y4f4w_{xy}=150y^{4}f^{4}.

Finally, wxyz=(wxy)zw_{xyz}=(w_{xy})_{z}, so wxyz=z(150y4f4)=150y4z(f4)=150y4.4f3fz=600y4f3.7z6w_{xyz}=\frac{\partial}{\partial z}\left(150y^{4}f^{4}\right)=150y^{4}\frac{% \partial}{\partial z}\left(f^{4}\right)=150y^{4}.4f^{3}\frac{\partial f}{% \partial z}=600y^{4}f^{3}.7z^{6}. Thus wxyz=4200y4z6(x+y5+z7)3w_{xyz}=4200y^{4}z^{6}(x+y^{5}+z^{7})^{3}.

W2.12. (i) Easy way (via implicit differentiation) Differentiating by xx and using the product rule, we obtain:

3x2y+x3dydx+2ydydx=0,3x^{2}y+x^{3}\frac{dy}{dx}+2y\frac{dy}{dx}=0,

hence, by rearranging, (x3+2y)dydx=-3x2y(x^{3}+2y)\frac{dy}{dx}=-3x^{2}y, so dydx=-3x2yx3+2y\frac{dy}{dx}=-\frac{3x^{2}y}{x^{3}+2y}.

Second way (similar to 2.9-10 in the notes) We can rearrange the equation to obtain: (y+x32)2=2+x64(y+\frac{x^{3}}{2})^{2}=2+\frac{x^{6}}{4}, hence y=-x3±8+x62y=\frac{-x^{3}\pm\sqrt{8+x^{6}}}{2}. Now we can differentiate to obtain dydx=12(-3x2±3x5(8+x6)-12)\frac{dy}{dx}=\frac{1}{2}\left(-3x^{2}\pm 3x^{5}(8+x^{6})^{\frac{-1}{2}}\right).

(ii) We take the partial derivatives with respect to SS on the left- and right-hand sides. Then we obtain:

rerS=2aaSS2+2a2Sre^{rS}=2a\frac{\partial a}{\partial S}S^{2}+2a^{2}S

so, rearranging, we obtain: 2aS2aS=rerS-2a2S2aS^{2}\frac{\partial a}{\partial S}=re^{rS}-2a^{2}S, whence aS=rerS-2a2S2aS2\frac{\partial a}{\partial S}=\frac{re^{rS}-2a^{2}S}{2aS^{2}}.

(iii) Once again, we take partial derivatives. Looking at each term in turn: on the left-hand side, q(pm)=mpq\frac{\partial}{\partial q}(pm)=m\frac{\partial p}{\partial q}, q(pq)=p+qpq\frac{\partial}{\partial q}(pq)=p+q\frac{\partial p}{\partial q} and q(qm)=m\frac{\partial}{\partial q}(qm)=m. On the right-hand side we obtain q(cos(pqm))=-q(pqm)sin(pqm)=-(pm+mqpq)sin(pqm)\frac{\partial}{\partial q}(\cos(pqm))=-\frac{\partial}{\partial q}(pqm)\sin(% pqm)=-(pm+mq\frac{\partial p}{\partial q})\sin(pqm). Thus

mpq+p+qpq+m=-(pm+mqpq)sin(pqm)m\frac{\partial p}{\partial q}+p+q\frac{\partial p}{\partial q}+m=-\left(pm+mq% \frac{\partial p}{\partial q}\right)\sin(pqm)

and so, rearranging, we get (m+q+mqsin(pqm))pq=-(m+p+mpsin(pqm))(m+q+mq\sin(pqm))\frac{\partial p}{\partial q}=-(m+p+mp\sin(pqm)). Rearranging, we obtain:

pq=-m+p+mpsin(pqm)m+q+mqsin(pqm).\frac{\partial p}{\partial q}=-\frac{m+p+mp\sin(pqm)}{m+q+mq\sin(pqm)}.

W2.13. (i) With f(x,y)=y/xf(x,y)=y/x we have first-order partial derivatives

fx=-y/x2, andfy=1/x,f_{x}=-y/x^{2},\quad{\hbox{and}}\quad f_{y}=1/x,

and second-order partial derivatives

fxx=2y/x3, fyy=0, fxy=-1/x2.f_{xx}=2y/x^{3},\quad f_{yy}=0,\quad f_{xy}=-1/x^{2}.

(ii) Recall that ddutan-1u=1/(1+u2){{d}\over{du}}\tan^{-1}u=1/(1+u^{2}). So with g(x,y)=tan-1(y/x),g(x,y)=\tan^{-1}(y/x), we have, by the chain rule and the results of (i), the first-order partial derivatives

gx=11+y2/x2(-y/x2)=-yx2+y2, gy=11+y2/x2(1/x)=xx2+y2,g_{x}={{1}\over{1+y^{2}/x^{2}}}(-y/x^{2})={{-y}\over{x^{2}+y^{2}}},\;\;g_{y}={% {1}\over{1+y^{2}/x^{2}}}(1/x)={{x}\over{x^{2}+y^{2}}},

and second-order partial derivatives

gxx=2xy(x2+y2)2, gyy=-2xy(x2+y2)2,g_{xx}={{2xy}\over{(x^{2}+y^{2})^{2}}},\quad g_{yy}={{-2xy}\over{(x^{2}+y^{2})% ^{2}}},
gxy=y(-y(x2+y2)-1)=-(x2+y2)-1+2y2(x2+y2)-2=y2-x2(x2+y2)2.g_{xy}={{\partial}\over{\partial y}}\Bigl(-y(x^{2}+y^{2})^{-1}\Bigr)=-(x^{2}+y% ^{2})^{-1}+2y^{2}(x^{2}+y^{2})^{-2}={{y^{2}-x^{2}}\over{(x^{2}+y^{2})^{2}}}.

In the final step it is slightly easier to use the product rule than the quotient rule.

W2.14. (i) By the quotent rule, we have

ddssechs=dds1coshs=-sinhscosh2s=-sechstanhs.{{d}\over{ds}}{\hbox{sech}}\,s={{d}\over{ds}}{{1}\over{\cosh s}}=-{{\sinh s}% \over{\cosh^{2}s}}=-{\hbox{sech}}\,s\tanh s.

(ii) With f(s)=-2-1sech2(s/2)f(s)=-2^{-1}{\hbox{sech}}^{2}(s/2), we have

f(s)=(-2-1)2sech(s/2)(-1/2)sech(s/2)tanh(s/2)=2-1sech2(s/2)tanh(s/2),f^{\prime}(s)=(-2^{-1})2{\hbox{sech}}\,(s/2)(-1/2){\hbox{sech}}(s/2)\tanh(s/2)% =2^{-1}{\hbox{sech}}^{2}(s/2)\tanh(s/2),

so

f(s)2=4-1sech4(s/2)tanh2(s/2),f^{\prime}(s)^{2}=4^{-1}{\hbox{sech}}\,^{4}(s/2)\tanh^{2}(s/2),

while

f2(2f+1)=4-1sech4(s/2)(1-sech2(s/2))=4-1sech4(s/2)tanh2(s/2);f^{2}(2f+1)=4^{-1}{\hbox{sech}}^{4}(s/2)(1-{\hbox{sech}}^{2}(s/2))=4^{-1}{% \hbox{sech}}^{4}(s/2)\tanh^{2}(s/2);

hence

(f)2=f2(2f+1).(f^{\prime})^{2}=f^{2}(2f+1).